Relevansi Penerapan Etika Guru dalam Perspektif Ki Hadjar Dewantara di Era Milenial - Puspakartika, Ananda; Syihabuddin, Syihabuddin (Jurnal Pendidikan dan Konseling (JPDK), 2022)
This study aims to find out about teacher ethics from the view of Ki Hadjar Dewantara. The relationship between teacher ethics in educational development and the role of teacher ethics in the present. This paper will also discuss the ethical values that are taught according to Ki Hadjar Dewantara and the relevance of implementation of teacher ethics from the perspective of Ki Hadjar Dewantara in the millennium era. This research uses a descriptive qualitative approach method. The research found three ethical principles of exemplary Ki Hajar Dewantara Ing Ngarso Sun Tulodo, In Madyo Mbangun Karso, Tut Wuri Handayani has such great impact if indeed the teachers carry out and apply the three ethical terms above from KHD in the millennium era. That an ethical teacher is a person of good character, that is, who can fulfil his true role and mandate as an educator. Teachers not only teach academic subjects but are encouraged to be able to provide motivation, encouragement and enthusiasm to their students in achieving their goals. From the perspective of Ki Hajar Dewantara, if ethics are applied in the way of life humans will come to the goal of a life of peace and happiness.